CATHOLIC SOCIAL TEACHING ON THE ROLE OF MODERN COMMUNICATION PROCESSES IN HARMONIZING THE INDIVIDUAL AND SOCIAL - Matyukhina, Oleksandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The article explores the peculiarities of understanding the issue of modern communicative processes and their role in harmonizing the individual and social in the social teaching of the Catholic Church. In the social teaching of the Catholic Church, considerable attention is paid to the analysis of modern communication processes and their role in transforming the social sphere. It sees them as a catalyst for harmonizing the relationship between the individual and social, noting their humanistic potential. The aim of this article is to outline the peculiarities of the Catholic Church’s approach to the issue of the possibilities of modern communication processes and their components in the humanization of the modern world and the harmonization of the individual and social. Research methods. To achieve the goal, methods of analysis and synthesis, systematization, comparative-axiological method, systemic and phenomenological approaches, and the principle of objectivity have been applied. Research results. It is emphasized that the Catholic Church, in its social teaching, pays significant attention to modern communication processes. It is noted that in the social teaching of the Catholic Church, modern communication processes are seen as a catalyst for a new relationship between the individual and social. It is highlighted that their radical transformation creates both threats and new opportunities. However, social teaching focuses more on the opportunities they create for overcoming the systemic crisis of modern civilization rather than the threats. The Catholic Church considers the leading aspect of modern communication processes to be their universal character and the inherent socio-creative humanistic potential. Discussion. The peculiarities of the Catholic Church’s communicative concept are analyzed in the works of many domestic and foreign scholars. They pay significant attention to the views of John Paul II on social communication and its means, and their role in the development of society. Conclusions. In conclusion, it is emphasized that the Catholic Church, from a Christian understanding of the world and humanity, optimistically evaluates modern communication processes and the development of information and communication technologies. It finds the new opportunities implied in them for the development of society based on the spread and affirmation of the principles of fraternity and solidarity, and universal moral values.